Forest in Hittite texts - Hasan Tuncer (Turkish Journal of Forestry, 2023)
Since the earliest times of history, fertile lands have had an important place for every society. This was also the case for the Hittites. Forested areas and the types of trees found in these areas are recorded in Hittite texts. The aim of this article is to analyses and evaluate the issue of forest in the Hittites through Hittite texts. In addition, the words that express the word forest and appear in the cuneiform documents were examined and how they were used in the texts was expressed. In the Hittites, forested areas with various trees were not only considered as a place of material benefits, but also as a sacred place. So much so that the Hittites performed many rituals in forested areas. It is also learnt from the texts that there were officials, bathing houses and some structures consecrated during the rituals in the forested areas. Some suggestions were also made to prevent the wrath and evil of the gods from visiting the forested areas. As various cities may have forests, sometimes forested areas were mentioned in the designation of a place, and sometimes it was stated that forests were located in an important part of the city. Forests, which were considered as a sacred place by the Hittites, were recorded in cuneiform documents in many different types of texts.